The Effectiveness of AI-Powered Sentiment Analysis in Corporate Communication in Improving Stakeholder Engagement - Ioseb Gabelaia; Migle Smaidziunaite (International Journal of Management, Knowledge and Learning)
Purpose: There is limited research on Artificial intelligence and its distinctive and measurable impact on corporate communication and stakeholder engagement. Besides, existing and new research frequently lacks industry-specific insights, practical case studies, and cross-disciplinary insights. This article is the first of two articles on corporate communication and artificial intelligence developed by the authors. This article explores the effectiveness of integrating artificial intelligence into corporate communication to improve stakeholder engagement.